2021
DOI: 10.3390/biomedicines9091124
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin as a Biomarker to Predict and Monitor Major Depressive Disorder Identified by Whole-Genome Transcriptomic Analysis in Mouse Models

Abstract: Background: Accumulations of stressful life events result in the onset of major depressive disorder (MDD). Comprehensive genomic analysis is required to elucidate pathophysiological changes and identify applicable biomarkers. Methods: Transcriptomic analysis was performed on different brain parts of a chronic mild stress (CMS)-induced MDD mouse model followed by systemic analysis. QPCR and ELISA were utilized for validation in mice and patients. Results: The highest numbers of genes with significant changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…An additional argument for the relevance of abnormal HPT function in depression is the finding that MDD patients exhibit significantly reduced blood levels of transthyretin (TTR), the protein thought to be partially responsible for thyroxine transport across the blood brain barrier [ 139 ]. TTR has been recently identified as a novel biomarker not only for MDD diagnosis but also for disease monitoring [ 139 ].…”
Section: Physiological Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional argument for the relevance of abnormal HPT function in depression is the finding that MDD patients exhibit significantly reduced blood levels of transthyretin (TTR), the protein thought to be partially responsible for thyroxine transport across the blood brain barrier [ 139 ]. TTR has been recently identified as a novel biomarker not only for MDD diagnosis but also for disease monitoring [ 139 ].…”
Section: Physiological Phenotypesmentioning
confidence: 99%
“…An additional argument for the relevance of abnormal HPT function in depression is the finding that MDD patients exhibit significantly reduced blood levels of transthyretin (TTR), the protein thought to be partially responsible for thyroxine transport across the blood brain barrier [ 139 ]. TTR has been recently identified as a novel biomarker not only for MDD diagnosis but also for disease monitoring [ 139 ]. TTR is drastically reduced in the hippocampus of selectively-bred Wistar Kyoto More Immobile (WMI) males, who exhibit depression-like behaviors, unlike the control Wistar Kyoto Less Immobile (WLI) rats [ 94 ].…”
Section: Physiological Phenotypesmentioning
confidence: 99%
“…Excitatory and inhibitory neurons from related brain regions were identified by the expression of specific markers ( Figure 5A ) ( Morarach et al, 2021 ). DEGs, such as Hsp90aa1, Pcdh11x, Vwa5a, and Ttr, which have been linked to depression in previous studies, have been found ( Crow, 2011 ; Xiang et al, 2018 ; Szabo et al, 2021 ; Yu et al, 2021 ). In total, 5110 neurons in the above 4 groups were obtained and classified into 12 subtypes ( Figure 5B ) based on the expression of specific markers ( supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 75%
“…In addition to alterations in Bdnf , Ttr and Neurod2 expression implicated in MDD and autism spectrum disorder (ASD), respectively [45,46], we detected some other genes implicated in psychiatric disorders. For instance, En2 (engrailed 2), an ASD-associated gene [47,48], was upregulated in ACC of phasic responders more than fivefold.…”
Section: Resultsmentioning
confidence: 99%